2019
DOI: 10.1038/s41598-019-50586-2
|View full text |Cite
|
Sign up to set email alerts
|

A variant of the castor zinc finger 1 (CASZ1) gene is differentially associated with the clinical classification of chronic venous disease

Abstract: Recent reports have suggested a reproducible association between the rs11121615 SNP, located within an intron of the castor zinc finger 1 (CASZ1) gene, and varicose veins. This study aimed to determine if this variant is also differentially associated with the various clinical classifications of chronic venous disease (CVD). The rs11121615 SNP was genotyped in two independent cohorts from New Zealand (n = 1876 controls /1606 CVD cases) and the Netherlands (n = 1626/2966). Participants were clinically assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…(11,57,58) Delineating the roles of the various genes implicated in VV pathogenesis is important and may lead to novel therapies, which could be targeted towards patients at risk of deterioration to chronic ulceration. (59) In this study we have identified a striking 'boundary' in the endothelial expression of Efnb2 at the site of developing VVs (meaning a demarcation between ephrinB2 lo upstream cells and ephrinB2 hi VFCs and cells immediately downstream), and that both ephrinB2 and EphB4 are required for normal organization of VFCs at this critical stage of development in mice. Since ephrinB2 remains the only known ligand for EphB4, this leads us to speculate that an ephrinB2-EphB4 interaction within venous endothelia regulates VV formation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…(11,57,58) Delineating the roles of the various genes implicated in VV pathogenesis is important and may lead to novel therapies, which could be targeted towards patients at risk of deterioration to chronic ulceration. (59) In this study we have identified a striking 'boundary' in the endothelial expression of Efnb2 at the site of developing VVs (meaning a demarcation between ephrinB2 lo upstream cells and ephrinB2 hi VFCs and cells immediately downstream), and that both ephrinB2 and EphB4 are required for normal organization of VFCs at this critical stage of development in mice. Since ephrinB2 remains the only known ligand for EphB4, this leads us to speculate that an ephrinB2-EphB4 interaction within venous endothelia regulates VV formation.…”
Section: Discussionmentioning
confidence: 66%
“…The extent of overlap of the genetic causes of VV failure and varicose veins is unclear since regulation of VVs is understudied, but some important indications of similarity have already emerged, including the identification of PPP3R1 and PIEZO1 in genome-wide association studies of varicose veins, and in mice as critical regulators of VV development ( 11 , 57 , 58 ). Delineating the roles of the various genes implicated in VV pathogenesis is important and may lead to novel therapies, which could be targeted toward patients at risk of deterioration to chronic ulceration ( 59 )…”
Section: Discussionmentioning
confidence: 99%
“…Yet the fact that rs11121615-T ( CASZ1 lead SNP) is the most significantly associated variant in the FinnGen data, indicates that the VV cases are not at least substantially confounded by the least severe form of VV, i.e. telangiectasia or reticular veins (C1 on the CEAP classification system 65 ), as earlier studies have observed this CASZ1 variant is not associated with these forms of venous disease 66 . The average age at the end of follow-up for VV controls was 12.2 and 10.7 years higher than the sex-specific VV diagnosis age for females and males (Supplementary Data 9 ).…”
Section: Methodsmentioning
confidence: 70%
“…CASZ1 and its related genes may promote the occurrence of stroke, which is of great significance for the treatment and prevention of stroke [90]. There is a reproducible association between rs11121615 SNP, located within an intron of CASZ1 gene, and chronic venous disease (CVD) [91][92][93]. In addition, the mutation frequency of SNPs rs10511083 of CASZ1 gene was significantly correlated with psoriasis [94].…”
Section: In Other Diseasesmentioning
confidence: 99%